Numerical Simulation of an Oscillating Water Column Wave Energy Converter: Comparison of two Numerical Codes - Conde, J. M. (2011)
This paper presents the results from the application of two numerical codes in the simulation of an oscillating water column wave energy converter. One of the codes (FLUINCO) is based on the finite elements technique, while the other (FLUENT) is based on the finite volume technique. The objective of this work is the validation of these codes for this type of flow, aiming the systematic application to wave energy converters design. The simulated case, corresponding to a simplified model tested experimentally, allows us to conclude that the numerical results have good quality, showing good correspondence between experimental and numerical results